Pengaruh Olahraga terhadap Mood dan Tingkat Stress Individu - Ayuna davatiansyah; Sharfina Rahma Sukma Aisyah; Ahmad Samsul Falah; Ruth Natalia Susanti (Program Studi Psikologi Islam, 2025)
This study aims to analyze the effect of exercise on mood and stress levels of individuals, especially in college students. The research method used is quantitative with a one group pretest-posttest design, involving seven participants selected through purposive sampling techniques based on certain criteria. The intervention in the form of light exercise for five minutes was carried out routinely for seven consecutive days. Measurements were carried out using positive and negative affect scale instruments before and after the intervention, as well as daily reflections to explore the subjective experiences of participants. The results showed that short exercise interventions can increase positive emotions and reduce negative emotions in some participants, especially those who have intrinsic motivation and positive perceptions of exercise. However, not all participants experienced significant changes, indicating that the effectiveness of the intervention is influenced by motivational factors, initial habits, and external psychological conditions. This study recommends exercise as a practical intervention to improve emotional well-being, taking into account mental readiness and personal meaning for individuals. These findings contribute to scientific understanding of the importance of a personal approach in implementing exercise for mental health.